1991
DOI: 10.1093/carcin/12.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of expression of virus-like elements following exposure of mice to high- and low-LET radiations

Abstract: Modulation of virus expression has been reported following exposure to a variety of cellular stresses, including UV radiation and heat-shock. The experiments reported here were designed to examine expression of endogenous VL30 (virus-like 30 S) elements following exposure of whole mice to ionizing radiations. Whole mice were exposed to doses of neutrons (50 cGy) or gamma-rays (300 cGy) shown to be equally efficient in cancer production in the whole animal, and tissues were harvested at 10 and 60 min following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Molecular data supporting this notion were derived from radium-and thorium-induced osteosarcomas showing new retroviral integrations in the DNA of the tumor cells but not in normal bone marrow cells of tumor-bearing mice [37], amplification and enhanced expression of the myc oncogene [40], mutations and rearrangements together with enhanced expression of the p53 tumor suppressor gene [39], and disruption of wt p53 gene function by retroviral insertion (Mitreiter et al, manuscript submitted). Similar observations were derived from y-irradiated cells, including the induction of endogenous retroviral sequences in tissues from irradiated mice [22] and cell lines [13] and induction of oncogenes [26], notably the fos oncogene [43], which in addition to its function as a member of the AP-I transcription factor complex has recently been shown to increase genomic instability [44]. These data suggest that proliferation-as well as differentiation-associated cellular genes represent critical targets for ionizing irradiation.…”
Section: Discussionsupporting
confidence: 63%
“…Molecular data supporting this notion were derived from radium-and thorium-induced osteosarcomas showing new retroviral integrations in the DNA of the tumor cells but not in normal bone marrow cells of tumor-bearing mice [37], amplification and enhanced expression of the myc oncogene [40], mutations and rearrangements together with enhanced expression of the p53 tumor suppressor gene [39], and disruption of wt p53 gene function by retroviral insertion (Mitreiter et al, manuscript submitted). Similar observations were derived from y-irradiated cells, including the induction of endogenous retroviral sequences in tissues from irradiated mice [22] and cell lines [13] and induction of oncogenes [26], notably the fos oncogene [43], which in addition to its function as a member of the AP-I transcription factor complex has recently been shown to increase genomic instability [44]. These data suggest that proliferation-as well as differentiation-associated cellular genes represent critical targets for ionizing irradiation.…”
Section: Discussionsupporting
confidence: 63%
“…Gene rearrangement is still not well understood at the molecular level in radiation-induced tumor cells. However, speculative data were presented that X-irradiation increased in the level of message for VL30-retro element which is also a member of the mouse retrotransposon family [26]. If IAP message is increased with VL30 mRNA, then frequency of incorporation can be increased.…”
Section: Rllllllll[llllllllllilllillllllmentioning
confidence: 99%
“…many studies have identified genes induced in response to DNA-damaging agents such as UV and ionizing radiation (Anderson and Woloschak 1992;Boothman et al 1991;Fornace et al 1988Fornace et al , 1989Fornace, 1992;Herrlich et al 1992;Hallahan et al 1989;Libertin et al 1994;Martin et al 1993;Munson and Woloschak 1990;Panozzo et al 1991;Peak et al 1991;Ramsamooj et al 1992;Ronai et al 1988;Stein et al 1989a, b;Valerie et al 1988;, 1992Woloschak et al 1990aWoloschak et al , b, c, 1994Woloschak et al , 1995aSakakeeny et al 1994). The collective contribution of these studies has led to the implication of several different transcription or regulatory elements as playing a key role in the immediate early response, including p53, AP-1, NF-~€3, and others (Hallahan et al 1991;Kastan et al 1991;Nelson and Kastan 1994;Sun et al 1995;Brach et al 1991;Angel et al 1987;Andahbi et al 1993;Kharbanda et al 1995;D a m et al 1992Mohan and Meltz 1994: Prasad et al 1994: Sahijdak et al 1994McKenna et al 1991), and the identification of nuclear and nonnuclear events as playing essential roles in the actual induction process (Stein et al 1989a, b;Uckun et al 1992Uckun et al , 1993Simon et al 1994;…”
Section: Introductionmentioning
confidence: 99%